2006
DOI: 10.1001/archfaci.8.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic vs Postoperative Antibiotic Use in Complex Septorhinoplasty Surgery

Abstract: Objective: To compare the efficacy of prophylactic vs postoperative antibiotic use in complex septorhinoplasty and strengthen the evidence base for antibiotic use in nasal surgery.Design: A randomized, prospective, single-blinded trial. One hundred sixty-four patients requiring complex septorhinoplasty surgery were recruited sequentially from the waiting lists of the 2 senior authors. Power was calculated at 80% at the 5% significance level. Patients randomized to the prophylactic arm of the study received thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 10 publications
(13 reference statements)
1
70
1
Order By: Relevance
“…Andrews et al, in a randomized study of 164 patients undergoing complex septorhinoplasty, reported that infection rates between the prophylactic (7%) and postoperative (11%) use of antibiotics groups were not significantly different. 16) However, they recommended the use of prophylactic antibiotics for patients undergoing complex septorhinoplasty. 16) One patient (case 8) complained of facial pain and headache when followed 9 days after the SMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrews et al, in a randomized study of 164 patients undergoing complex septorhinoplasty, reported that infection rates between the prophylactic (7%) and postoperative (11%) use of antibiotics groups were not significantly different. 16) However, they recommended the use of prophylactic antibiotics for patients undergoing complex septorhinoplasty. 16) One patient (case 8) complained of facial pain and headache when followed 9 days after the SMR.…”
Section: Discussionmentioning
confidence: 99%
“…16) However, they recommended the use of prophylactic antibiotics for patients undergoing complex septorhinoplasty. 16) One patient (case 8) complained of facial pain and headache when followed 9 days after the SMR. The patient discontinued antiplatelet drugs for 5 days before surgery and took it again after surgery for prevention of cardiovascular accidents.…”
Section: Discussionmentioning
confidence: 99%
“…7 While the risk of postoperative infection after rhinoplasty is generally low, perioperative antibiotics may minimize the risk of postoperative infection after rhinoplasty, though questions persist surrounding duration. 17,18 …”
Section: External Nasal Valvementioning
confidence: 99%
“…In order to prevent the development of side effects and resistance, antimicrobial prophylaxis should be discontinued as soon as possible even if drains, catheters or implants have been used in breast and plastic surgery operations (4,5,11,16,19,28). In breast surgery, any significant differences were not found between single dose antimicrobial prophylaxis regimens and extended protocols in terms of wound infection (5,11,19).…”
Section: Duration Of Prophylaxismentioning
confidence: 99%